Carotenoid–chlorophyll energy transfer in the fucoxanthin–chlorophyll complex binding a fucoxanthin acyloxy derivative. (23rd April 2019) - Staleva-Musto, Hristina; West, Robert; Trathnigg, Marco; Bína, David; Litvín, Radek; Polívka, Tomáš
Abstract : A fucoxanthin derivative has negligible charge-transfer character of the S1 /ICT state resulting in slowing down of the carotenoid–chlorophyll energy transfer. Abstract : The fucoxanthin–chlorophyll a protein from Emiliania huxleyi (E-FCP) is a member of the LHC family of light-harvesting proteins. It has a rather unusual pigment composition as its binds more Chl- c than Chl- a, and 19′-hexanoyloxyfucoxanthin (hFx) as the main carotenoid instead of fucoxanthin (Fx) typically found in various FCP complexes. The presence of a hexanoyloxy tail in hFx suppresses the charge transfer character of the S1 /ICT state resulting in almost no effect of polarity on the excited state dynamics of hFx, strongly contrasting with the excited-state properties of Fx. Here we report on the dynamics of the energy transfer between hFx and Chl in E-FCP, and we compare it with Fx–Chl energy transfer in the FCP complex from Phaeodactylum tricornutum . In both complexes, the excited hFx (Fx) transfers energy from the S2 state with a sub-100 fs time constant and no effect of the hexanoyloxy tail on the efficiency of the S2 route was found. The energy transfer via the S1 /ICT state has in E-FCP two channels characterized by 1.5 and 11 ps time constants, while for FCP these two channels operate with time constants of 0.8 and 4.5 ps. Thus, minimizing the charge transfer character of S1 /ICT in hFx results in about twice slower energy transfer via the S1 /ICT state, underlining the importance of the ICT state in facilitating carotenoid–Chl energy transfer in systems utilizing keto carotenoids as energy donors.